Biochemical characteristics and in vitro degradability of sunflower seed hull and wheat straw treated with Pleurotus ostreatus and Ganoderma sessile - Maximiliano Andrés Bidegain; Celeste Lentz; Rabotnikof, Celia; Roberto Distel; Pablo Postemsky (Agriculture and Natural Resources, 2026)
Importance of the work: Exploring sustainable uses for regional agricultural residues can address the need for eco-friendly solutions in livestock feeding. Objectives: To evaluate the potential of Pleurotus ostreatus and Ganoderma sessile to transform sunflower seed hulls (SSH) and wheat straw and to enhance their in vitro digestibility. Materials and Methods: SSH and wheat straw were treated with Pleurotus ostreatus (strains A01, PPWarm, P04, P0761, P07) and Ganoderma sessile strain E47. Colonization time, enzyme activity, phenolic compounds content, reducing sugar content, fiber composition and in vitro digestibility (IVD) were assessed, along with the impact of the inoculum formulation on these variables. Results: Fungal strains colonized substrates within 10–25 d. Laccase activity was in the ranges 2,266–4,621 U/kg in SSH and 1,135–7,279 U/kg in wheat straw. Peroxidase activity was in the range 0–490 U/kg. In SSH, reducing sugars increased, with G. sessile E47 producing a 164% increase (p < 0.001). In contrast, in wheat straw, reducing sugars decreased, with P. ostreatus P04 reducing the content by 64% (p < 0.001). The phenolic and triterpenoid contents decreased across all treatments. Fiber content changes were substrate-dependent—in the SSH, neutral detergent fiber and acid detergent fiber fractions, increased by 14.1–21.6%, while in the wheat straw, changes were minimal. IVD remained unchanged for most treatments, except for P. ostreatus PPWarm (-20.7%, p = 0.013) and G. sessile E47 (-60.9%, p < 0.001) on SSH. Inoculum formulation without grains altered mycelial effects on substrate degradation, increasing SSH digestibility by 70.5% (p = 0.003) after treatment with P. ostreatus A01. Main finding: The fungal treatments modified the SSH and wheat straw composition, with digestibility improvement critically dependent on inoculum type and substrate.